Significant insights into the operation of DC-link voltage control of a shunt active power filter using different control algorithms: a comparative study - Abdul Rahman, Nor Farahaida; Mohd Radzi, Mohd Amran; Che Soh, Azura; Mariun, Norman; Abd Rahim, Nasrudin (Scientific and Technological Research Council of Turkey, 2017)
A comparative study between a conventional DC-link voltage control algorithm (CDVCA) and a self-charging DC-link voltage control algorithm (SDVCA) is presented. It focuses on the principle operation of both algorithms and their impacts on the performance of a shunt active power filter (SAPF) operation. All analyses are based on the step response of DC-link voltages under different start-up times of the SAPF and different initial DC-link voltage values. Other considered parameters are the ripple factor (RP) of DC-link voltages, estimated and measured DC-link charging currents, and total harmonic distortion (THD) value of supply currents. Thus, this study provides new insights into the operation of DC-link voltage control using different control algorithms. According to the simulation results, the SAPF using the SDVCA has shown better performance than using the CDVCA. By using the SDVCA, the charging process of a DC-link capacitor starts almost instantaneously. Additionally, the overshoot, settling time, and RF of DC-link voltages are reduced. Other than that, THD values of supply currents are improved, by generating low ripple of estimated DC-link charging currents. Experimental validation of the SAPF using the SDVCA is also presented.